Guidelines for Promoting Local Food Identity for Creative Gastronomic Tourism: A Case Study of Danchak sub-district, Nonthai district, Nakhonratchasima Province - Klinjandang, Katika; Jaisamran, Arnut; Samranrat, Napat (Journal of Management Science Nakhonratchasima University, 2025)
This study was a qualitative research that aimed to explore the identity of local food for the purpose of promoting creative gastronomic tourism and to propose guidelines for enhancing local food identity in support of creative gastronomic tourism. The study was conducted as a case study of Danchak Sub-district, Nonthai District, Nakhon Ratchasima Province. The research employed a semi-structured interview form to collect data from 20 key informants, comprising 5 representatives from relevant government agencies and 15 local residents of Danchak Sub-district, Nonthai district, Nakhonratchasima province The findings revealed that Nam Tab represented the local food identity of Danchak Sub-district, Nonthai district, Nakhonratchasima province and reflected the lifestyle and food culture of the community. The identity of this local cuisine encompassed 4 main dimensions: 1) Symbolic Dimension ; 2) Structural Dimension ; 3) Social Dimension; and (4) Spatial Dimension. The proposed guidelines for promoting local food identity to support creative gastronomic tourism included : 1) establishing local food entrepreneur groups to enhance collaboration and production capacity; 2) developing packaging to increase product appeal and market competitiveness; 3) promoting local food products to raise awareness among target customer groups, and 4) organizing training programs to enhance the quality and standards of local food products.